Solid phase extractant and method for producing the same

JP2025022801APending Publication Date: 2025-02-14NIPPON ELECTRIC GLASS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024121912
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-03
Filing Date
2024-07-29
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0019】 本発明によれば、食品中の残留農薬分析において夾雑成分の吸着能が高い固相抽出剤及びその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022801000001
    Figure 2025022801000001
  • Figure 2025022801000002
    Figure 2025022801000002
  • Figure 2025022801000003
    Figure 2025022801000003
Patent Text Reader

Abstract

To provide a solid phase extractant with high adsorption capacity for undesired components in the analysis of pesticide residues in food, and a method for producing the same.SOLUTION: A solid phase extractant comprises porous glass particles, with a glass composition comprising SiO2 and ZrO2.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid-phase extraction agent and a method for producing the same. [Background technology]

[0002] For the analysis of pesticide residues in food, the QuEChERS (Quick, Easy, Cheap, Effective, Rugged, Safe) method, which is excellent in terms of the speed and simplicity of the test, has become widespread worldwide. Since the amount of pesticide residues in food is very small, it is extremely important in pesticide residue analysis to remove impurities that may interfere with the measurement in advance. Therefore, in most cases, the QuEChERS method involves extracting components containing pesticide residues from food by salting out, and then adding a solid-phase extraction agent to remove impurities in the extract. Finally, pesticide residues are simultaneously analyzed using measuring instruments such as GC-MS / MS or LC-MS / MS (Non-Patent Documents 1, 2). [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] M. Anastassiades et al., “Fast and Easy Multiresidue Method Employing Acetonitrile Extraction / Partitioning and “Dispersive Solid-Phase Extraction” for the Determination of Pesticide Residues in Produce,” J. AOAC Int., 86, 412 (2003). [Non-Patent Document 2] Ministry of Health, Labour and Welfare, "Guidelines for the evaluation of validity of test methods for pesticide residues in food," (November 15, 2007) (Food Safety Notification No. 1115001) Summary of the Invention [Problem to be solved by the invention]

[0004] Porous powders such as ethylenediamine-N-propylated silica gel (PSA), octadecylsilylated silica gel (ODS), and graphite carbon black (GCB) are used as solid-phase extraction agents in the QuEChERS method. PSA is effective in removing sugars, fatty acids, organic acids, lipids, and polar pigments from foods, ODS in removing lipids, sterols, and hydrophobic compounds, and GCB in removing pigments and polar compounds. However, in foods that contain a large amount of impurities that can interfere with the measurement, the removal is insufficient, making accurate analysis of residual pesticides difficult.

[0005] In view of the above, an object of the present invention is to provide a solid-phase extraction agent having a high adsorption capacity for impurity components in the analysis of pesticide residues in food, and a method for producing the same. [Means for solving the problem]

[0006] As a result of various experiments, the present inventors have found that a solid-phase extraction agent having a strong solid acidity can sufficiently adsorb impurity components.

[0007] Various aspects of a solid-phase extraction agent and a method for producing the same that solve the above problems will be described below.

[0008] The solid-phase extraction agent of the first aspect is characterized in that it is made of porous glass particles and contains SiO2 and ZrO2 as a glass composition.

[0009] The solid-phase extraction agent of the second embodiment is preferably the same as that of the first embodiment, and contains, in mass %, 70 to 95% SiO2, more than 0 to 25% ZrO2, 0 to 10% Al2O3, and 0 to 15% B2O3 + Na2O + K2O + CaO + P2O5 + TiO2 as a glass composition.

[0010] The solid-phase extraction agent of the third embodiment preferably contains, in the second embodiment, the following glass composition by mass: 70-90% SiO2, 10-25% ZrO2, 0-10% Al2O3, and 0-15% B2O3+Na2O+K2O+CaO+P2O5+TiO2.

[0011] The solid-phase extraction agent of Aspect 4 is any one of Aspects 1 to 3, and preferably has a substantially spherical particle shape.

[0012] In the solid-phase extraction agent of embodiment 5, in any one of embodiments 1 to 4, the average particle diameter D 50 It is preferable that the diameter of the porous layer is 0.1 to 300 μm and the pore size is 1 to 1000 nm.

[0013] The solid-phase extraction agent of embodiment 6 is any one of embodiment 1 to embodiment 5, wherein the specific surface area is 10 to 800 m 2 It is preferred that the molecular weight is / g.

[0014] The solid-phase extraction material of Aspect 7, in any one of Aspects 1 to 6, preferably has hydrophobic functional groups on the inner surface of the pores.

[0015] In the solid-phase extraction agent of Aspect 8, in Aspect 7, the hydrophobic functional group is preferably an octadecylsilyl group and / or a trimethylsilyl group.

[0016] The solid-phase extraction agent of Aspect 9 is preferably used in any one of Aspects 1 to 8 for residual pesticide analysis.

[0017] In the solid-phase extraction agent of Aspect 10, in Aspect 9, the pesticide residue analysis is preferably performed by the QuEChERS method or the STQ method.

[0018] The method for producing a solid-phase extraction agent of embodiment 11 is a method for producing a solid-phase extraction agent of any one of embodiments 1 to 10, and preferably includes a base material preparation step of preparing a glass base material, a precursor production step of obtaining precursor particles by crushing the glass base material, a porosity formation step of heat-treating the precursor particles to separate them into two phases, and then removing one of the phases with an acid solution to obtain porous glass particles, and a surface modification step using a silane coupling agent. Effect of the Invention

[0019] According to the present invention, it is possible to provide a solid-phase extraction agent having a high adsorption capacity for impurity components in the analysis of pesticide residues in food, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Preferred embodiments will be described below. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments.

[0021] <Solid phase extraction agent> The solid-phase extraction agent of the present invention is made of porous glass particles, and contains SiO2 and ZrO2 as a glass composition. More specifically, the porous glass particles preferably contain, in mass%, SiO2 70-95%, ZrO2 0-25%, Al2O3 0-10%, and B2O3+Na2O+K2O+CaO+P2O5+TiO2 0-15% as a glass composition. The reason for limiting the glass composition in this way will be explained below. In the following explanation, "%" means "mass%" unless otherwise specified. In the following explanation, the solid-phase extraction agent may be referred to as porous glass particles.

[0022] SiO2 is the main component of the network-forming oxide in the porous glass particles. The content of SiO2 is preferably 70 to 95%. More specifically, the lower limit of the content of SiO2 is preferably 70% or more, 75% or more, 80% or more, and particularly 81% or more. The upper limit of the content of SiO2 is preferably 95% or less, 90% or less, and particularly 85% or less. If the content of SiO2 is too low, it becomes difficult to chemically bond octadecylsilyl groups (ODS groups) or trimethylsilyl groups (TMS groups) to the surface of the porous glass particles. In addition, the weather resistance and mechanical strength of the porous glass particles tend to decrease. If the content of SiO2 is too high, the solid acidity of the porous glass particles becomes weak, and the effect of removing impurities in food is reduced.

[0023] ZrO2 is a component that exerts the solid acidity of the porous glass particles and obtains the effect of removing impurities in food. It is also a component that enhances the mechanical strength of the porous glass particles. The content of ZrO2 is preferably more than 0 to 25%, more preferably 10 to 25%. More specifically, the lower limit of the content of ZrO2 is preferably more than 0, 0.1% or more, 1% or more, 3% or more, 5% or more, 7% or more, 9% or more, 10% or more, and particularly preferably 10.1% or more. The upper limit of the content of ZrO2 is preferably 25% or less, particularly preferably 20% or less. If the content of ZrO2 is too low, the above effect cannot be obtained. If the content of ZrO2 is too high, it becomes difficult to chemically bond octadecylsilyl groups (ODS groups) or trimethylsilyl groups (TMS groups) to the surface of the porous glass particles.

[0024] Al2O3 is a component that improves the weather resistance and mechanical strength of the porous glass particles. The content of Al2O3 is preferably 0 to 10%. More specifically, the lower limit of the content of Al2O3 is preferably 0% or more, 0.1% or more, 0.5% or more, and particularly preferably 1% or more. The upper limit of the content of Al2O3 is preferably 10% or less, and particularly preferably 5% or less. If the content of Al2O3 is too high, the mechanical strength of the porous glass particles tends to decrease.

[0025] From the viewpoint of improving the weather resistance and mechanical strength of the porous glass particles, B2O3+Na2O+K2O+CaO+P2O5+TiO2 (the total content of B2O3, Na2O, K2O, CaO, P2O5 and TiO2) is preferably 0 to 15%. More specifically, the upper limit of the content of B2O3+Na2O+K2O+CaO+P2O5+TiO2 is preferably 15% or less, 10% or less, 8% or less, particularly 5% or less. The lower limit of the content of B2O3+Na2O+K2O+CaO+P2O5+TiO2 may be, for example, 0% or more, particularly 0.1% or more. The preferred ranges of the contents of each of the components B2O3, Na2O, K2O, CaO, P2O5 and TiO2 are as follows:

[0026] The upper limit of the B2O3 content is preferably 15% or less, 10% or less, 8% or less, 5% or less, 3% or less, 2% or less, particularly preferably 1% or less. The lower limit of the B2O3 content may be, for example, 0% or more, particularly preferably 0.1% or more.

[0027] The upper limit of the Na2O content is preferably 15% or less, 10% or less, 8% or less, 5% or less, 3% or less, particularly preferably 1% or less. The lower limit of the Na2O content may be, for example, 0% or more, particularly preferably 0.1% or more.

[0028] The upper limit of the K2O content is preferably 15% or less, 10% or less, 8% or less, 5% or less, 3% or less, particularly preferably 1% or less. The lower limit of the K2O content may be, for example, 0% or more, particularly preferably 0.1% or more.

[0029] The upper limit of the content of RO (R is any one selected from Mg, Ca, Sr, and Ba) is preferably 15% or less, 10% or less, 8% or less, 5% or less, and particularly preferably 3% or less. The lower limit of the content of RO is, for example, preferably 0% or more, and particularly preferably 0.1% or more. When at least two or more components selected from MgO, CaO, SrO, and BaO are contained, the upper limit of their total content is preferably 15% or less, 10% or less, 8% or less, 5% or less, and particularly preferably 3% or less, and the lower limit of their total content is preferably 0% or more, and particularly preferably 0.1% or more.

[0030] The upper limit of the P2O5 content is preferably 15% or less, 10% or less, 8% or less, 5% or less, particularly preferably 3% or less. The lower limit of the P2O5 content may be, for example, 0% or more, particularly preferably 0.1% or more.

[0031] The upper limit of the TiO2 content is preferably 15% or less, 10% or less, 8% or less, 5% or less, particularly preferably 3% or less. The lower limit of the TiO2 content may be, for example, 0% or more, particularly 0.1% or more, and from the viewpoint of increasing the mechanical strength of the glass skeleton, the lower limit of the TiO2 content is preferably 0.1% or more.

[0032] In addition to the above components, the porous glass particles may contain Li2O, ZnO, La2O3, Ta2O5, TeO2, Nb2O5, Gd2O3, Y2O3, Eu2O3, Sb2O3, SnO2, Bi2O3, etc. in an amount of 15% or less, 10% or less, 5% or less, particularly 3% or less, or in a total amount of 20% or less.

[0033] In addition, since PbO is an environmentally hazardous substance, it is preferable that it is not substantially contained. Here, "substantially not contained" means that it is not intentionally contained as a raw material, and objectively refers to a content of less than 0.1%.

[0034] It is preferable that the porous glass particles have solid acidity. If the solid-phase extraction agent has a strong solid acidity, it can sufficiently adsorb impurity components. Specifically, the lower limit of the acid amount of the solid acid is 0.05 μmol / m, as the amount of NH3 desorption measured by the ammonia temperature programmed desorption spectrometry (NH3-TPD method). 2 More than 0.1μmol / m 2 More than 0.5μmol / m 2 More than 0.15μmol / m 2 Above 0.20 μmol / m 2 The upper limit of the amount of acid is preferably 10 μmol / m 2 Below, 8μmol / m 2 Below, 6μmol / m 2 Below, 4μmol / m 2 Below, especially 2 μmol / m 2It is preferable that the acid amount of the solid acid is less than 50°C. If the acid amount of the solid acid is too small, it is difficult to obtain the effect of removing impurities in food. If the acid amount of the solid acid is too large, residual pesticides other than the intended impurities may be strongly adsorbed, and the purification effect of the residual pesticides may be reduced. In addition, the strength of the solid acid is preferably 50°C or more, 65°C or more, 80°C or more, particularly 100°C or more, and is preferably 1000°C or less, 900°C or less, 800°C or less, 600°C or less, particularly 400°C or less, at the peak temperature of the high-temperature peak in the NH3-TPD spectrum. If the strength of the solid acid is too small, it is difficult to obtain the effect of removing impurities in food. If the strength of the solid acid is too large, residual pesticides other than the intended impurities may be strongly adsorbed, and the purification effect of the residual pesticides may be reduced.

[0035] The porous glass particles preferably have Lewis acid sites and / or Bronsted acid sites on their surfaces. The presence of Lewis acid sites and / or Bronsted acid sites enables the adsorption of impurity components in food by utilizing acid-base interactions, and the purification effect of residual pesticides can be improved. High purification effect of residual pesticides enables more accurate analysis of residual pesticides. More preferably, the porous glass particles preferably have Lewis acid sites on their surfaces. The presence of Lewis acid sites allows the effective adsorption of impurity components such as lipids, fats, and pigments by Lewis acid-base interactions, and the purification effect of residual pesticides can be improved.

[0036] The Lewis acid sites and / or Bronsted acid sites on the surface of the porous glass particles can be measured, for example, by pyridine adsorption FT-IR. Specifically, pyridine is adsorbed on a porous glass sample, and the pyridine adsorption spectrum of the sample is measured. By observing the absorption peak of pyridine that is thought to be adsorbed on the Lewis acid sites and the absorption peak of pyridinium ions that are thought to be generated by proton donation from the Bronsted acid sites in the spectrum, the presence or absence of Lewis acid sites and / or Bronsted acid sites on the surface of the porous glass particles can be confirmed.

[0037] The solid-phase extraction agent of the present invention is preferably made of porous glass particles having a substantially spherical particle shape. By making the particles substantially spherical, it is possible to improve compatibility with organic solvents and increase dispersibility. Here, "substantially spherical" does not mean only true spheres, but refers to porous glass particles having a spherical shape in which the value obtained by dividing the shortest diameter passing through the center of gravity of the porous glass particles by the longest diameter is 0.5 or more, preferably 0.7 or more, and particularly preferably 0.9 or more.

[0038] The average particle size of the porous glass particles is preferably 0.1 to 300 μm. More specifically, the lower limit of the average particle size is preferably 0.1 μm or more, 0.3 μm or more, 0.5 μm or more, and particularly preferably 1 μm or more, and the upper limit of the average particle size is preferably 300 μm or less, 100 μm or less, 30 μm or less, 20 μm or less, and particularly preferably 10 μm or less. If the average particle size is too small, it becomes difficult to effectively separate the porous glass particles from an organic solvent such as acetonitrile in a short time during centrifugation after the purification process of residual pesticides. If the average particle size is too large, it becomes difficult to disperse the porous glass particles well in an organic solvent such as acetonitrile during the purification process of residual pesticides. The average particle size is D 50 (Volume-based average particle size) and refers to the value measured by laser diffraction scattering method.

[0039] The pore diameter (mode diameter in the pore distribution) of the porous glass particles is preferably 1 to 1000 nm. More specifically, the lower limit of the pore diameter is preferably 1 nm or more, 3 nm or more, 10 nm or more, 11 nm or more, particularly 12 nm or more, and the upper limit of the pore diameter is preferably 1000 nm or less, 500 nm or less, 100 nm or less, 80 nm or less, or 50 nm or less. If the pore diameter is too small, it is difficult for compounds such as impurity components to enter the pores, making it difficult to use the particles as a solid-phase extraction agent. On the other hand, if the pore diameter is too large, the specific surface area becomes small, and the adsorption ability of the porous glass particles decreases, making it difficult to use the particles as a solid-phase extraction agent.

[0040] The specific surface area of ​​porous glass particles is 10 to 800 m 2More specifically, the lower limit of the specific surface area is preferably 10 m 2 / g or more, 30m 2 / g or more, 50m 2 / g or more, especially 100m 2 / g or more, and the upper limit of the specific surface area is 800 m 2 / g or less is preferable. If the specific surface area of ​​the porous glass particles is too small, the adsorption ability of the porous glass particles decreases, making it difficult to use them as a solid-phase extraction agent. If the specific surface area of ​​the porous glass particles is too large, residual pesticides other than the target impurity components may also be strongly adsorbed, which may reduce the purification effect of residual pesticides.

[0041] As described above, the porous glass particles having the above composition and characteristics have a strong solid acidity and therefore a high ability to adsorb impurity components.

[0042] The inner pore surface of the porous glass particles is preferably modified with a hydrophobic functional group. The hydrophobic functional group is preferably an octadecylsilyl group (ODS group) and / or a trimethylsilyl group (TMS group). By chemically modifying the inner pore surface of the porous glass particles with an ODS group (ODS conversion), the impurity components in the food can be retained by utilizing hydrophobic interactions, and the effect of removing the impurity components can be improved. In addition, by performing end-capping treatment, the number of remaining silanol groups on the surface of the porous glass particles is reduced, and therefore the adsorption of pesticide components to the remaining silanol groups can be suppressed. When the ODS conversion treatment and end-capping treatment are performed on the porous glass particles, the solid-phase extraction agent contains both ODS groups and TMS groups on the inner pore surface.

[0043] As described above, the solid-phase extraction agent of the present invention is made of porous glass particles having the above-mentioned structure, and thus strongly adsorbs impurities that may interfere with residual pesticide analysis, and exhibits a high removal effect. It is particularly suitable as an adsorbent for use in the purification process of residual pesticides in the QuEChERS method and the STQ (Solid Phase Extraction Technique with QuEChERS) method.

[0044] <Method of manufacturing solid phase extraction agent> The method for producing a solid-phase extraction agent of the present invention is characterized by comprising a base material preparation step of preparing a glass base material, a precursor production step of obtaining precursor particles by crushing the glass base material, a porosification step of heat-treating the precursor particles to separate them into two phases, and then removing one of the phases with an acid solution to obtain porous glass particles, and a surface modification step using a silane coupling agent.

[0045] (Base material preparation process) In the base material preparation step, a glass base material is prepared. For example, a glass base material is obtained by melting and forming a glass raw material. First, the glass raw material is melted at 1300 to 1600°C for 2 to 12 hours. The glass base material preferably contains, for example, by mass%, 30 to 70% SiO2, more than 0 to 40% B2O3, 0 to 20% Li2O, 0 to 20% Na2O, 0 to 20% K2O, 50 to 10% P2O, more than 30% ZrO2, 0 to 20% Al2O3, 0 to 20% RO (R is at least one selected from Mg, Ca, Sr, and Ba), and 0 to 10% TiO2.

[0046] (Precursor preparation process) Next, the glass base material is pulverized to obtain precursor particles. Specifically, the glass base material is pulverized using a ball mill or the like to obtain precursor particles. After pulverization, precursor particles having a desired average particle size can be obtained by performing classification as necessary. The obtained precursor particles are heated at 1000 to 3000°C using a burner or the like to soften and flow, thereby becoming approximately spherical.

[0047] (Porous process) Next, the precursor particles are heat-treated to separate into two phases, and one of the phases is removed with an acid to obtain porous glass particles. More specifically, the precursor particles are heat-treated to separate into two phases, a silica-rich phase and a boron oxide-rich phase (spinodal phase separation), and the boron oxide-rich phase is removed with an acid to obtain porous glass particles.

[0048] The heat treatment temperature of the precursor particles is preferably 500 to 800°C, 600 to 780°C, and particularly preferably 650 to 780°C. If the heat treatment temperature is too high, the precursor particles may be softened and deformed. On the other hand, if the heat treatment temperature is too low, it is difficult to separate the precursor particles into phases. The heat treatment time is preferably 1 minute or more, 10 minutes or more, 30 minutes or more, and particularly preferably 1 hour or more. If the heat treatment time is too short, it is difficult to separate the precursor particles into phases. There is no particular upper limit to the heat treatment time, but since once phase separation has progressed to a certain extent, the phase separation state will not change significantly even if the heat treatment is continued for a longer period, it is practically 180 hours or less.

[0049] When carrying out the heat treatment, it is preferable to mix inorganic nanoparticles with the precursor particles. This makes it possible to suppress fusion between the precursor particles. Examples of inorganic nanoparticles include alumina fine particles and zirconia fine particles, and it is particularly preferable to use alumina particles. Average particle diameter D of inorganic nanoparticles 50 The average particle size of the inorganic nanoparticles is preferably 1 to 100 nm, 5 to 50 nm, and particularly preferably 10 to 40 nm. If the average particle size of the inorganic nanoparticles is too small, they tend to aggregate and become difficult to handle. On the other hand, if the average particle size of the inorganic nanoparticles is too large, it becomes difficult to obtain the effect of suppressing fusion between the precursor particles.

[0050] The amount of inorganic nanoparticles added is preferably 0.5 parts by mass or more, 1 part by mass or more, particularly 2 parts by mass or more, relative to 100 parts by mass of the precursor particles. If the amount of inorganic nanoparticles added is too small, it is difficult to obtain the effect of suppressing the fusion of the precursor particles. In addition, when the average particle diameter of the precursor particles is small, the precursor particles tend to fuse together, so it is preferable to increase the amount of inorganic nanoparticles added. Specifically, the amount of inorganic nanoparticles added may be 5 parts by mass or more, 10 parts by mass or more, 20 parts by mass or more, particularly 25 parts by mass or more. There is no particular limit to the upper limit of the amount of inorganic nanoparticles added, but since it is difficult to obtain further effects even if it is too large, it is preferable to set it to 100 parts by mass or less, and more preferably 80 parts by mass or less.

[0051] In the step of phase-separating the precursor particles, an altered layer (a silica-rich layer containing approximately 80 mol% or more of silica) may be formed on the surface of the precursor particles. In this case, it is preferable to remove the altered layer by immersing the precursor particles in hydrofluoric acid for a short period of time (e.g., 1 second to 10 minutes).

[0052] Next, the precursor particles separated into two phases are immersed in an acid solution to remove the boron oxide-rich phase, thereby obtaining porous glass particles. As the acid solution, hydrochloric acid or nitric acid is preferably used, and these acid solutions may be used in combination. The concentration of the acid solution is preferably 0.1 to 5 mol / L, particularly preferably 0.5 to 3 mol / L. The immersion time in the acid solution is preferably 0.1 hours or more, particularly preferably 0.2 hours or more. If the immersion time is too short, etching becomes insufficient, making it difficult to obtain porous glass particles having the desired pore size, pore volume, or specific surface area. If the immersion time is too long, the precursor particles may dissolve in the acid solution, so the upper limit of the immersion time is preferably 50 hours or less, 40 hours or less, 30 hours or less, 20 hours or less, particularly preferably 10 hours or less. The immersion temperature is preferably 20°C or more, 25°C or more, particularly preferably 30°C or more. If the immersion temperature is too low, etching becomes insufficient, making it difficult to obtain porous glass particles having the desired continuous pores. The upper limit of the immersion temperature is not particularly limited, but in practice it is 99° C. or lower.

[0053] In addition, the precursor particles from which the boron oxide-rich phase has been removed with acid have a structure in which SiO2 gel and ZrO2 gel derived from the boron-rich phase are deposited in the pores. Therefore, in addition to the removal of the boron oxide-rich layer, it is preferable to perform additional etching with an acid solution and an alkaline solution. This makes it possible to obtain porous glass particles that reflect a phase-separated structure.

[0054] The ZrO2 gel can be removed, for example, by immersing the precursor particles in sulfuric acid. The concentration of sulfuric acid is preferably 0.1 to 5 mol / L, particularly 1 to 5 mol / L. The immersion time in sulfuric acid is preferably 0.1 hours or more, particularly 0.2 hours or more. If the immersion time is too short, it becomes difficult to remove the ZrO2 gel. There is no particular upper limit to the immersion time, but it is practically 20 hours or less, and further 10 hours or less. The immersion temperature is preferably 20°C or more, 25°C or more, particularly 30°C or more. If the immersion temperature is too low, it becomes difficult to remove the ZrO2 gel. There is no particular upper limit to the immersion temperature, but it is practically 99°C or less.

[0055] The SiO2 gel can be removed, for example, by immersing the precursor particles in an alkaline solution. As the alkaline solution, an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, or the like can be used. These alkaline solutions may be mixed and used. The concentration of the alkaline solution is preferably 0.1 to 5 mol / L, particularly 0.5 to 3 mol / L. The immersion time in the alkaline solution is preferably 0.1 hours or more, particularly 0.2 hours or more. If the immersion time is too short, it becomes difficult to remove the SiO2 gel. There is no particular limit to the upper limit of the immersion time, but it is practically 20 hours or less, and further 10 hours or less. The immersion temperature is preferably 15°C or more, particularly 20°C or more. If the immersion temperature is too low, it becomes difficult to remove the SiO2 gel. There is no particular limit to the upper limit of the immersion temperature, but it is practically 99°C or less.

[0056] (Surface modification process) In the surface modification step, the surface is modified using a silane coupling agent. More specifically, it is preferable to thoroughly dry the porous glass particles at a temperature of 100° C. or higher, and then use a silane coupling agent such as dimethyloctadecylchlorosilane or octadecyltrichlorosilane to chemically bond ODS groups to the surface of the porous glass particles under toluene reflux. It is also preferable to use pyridine as a catalyst in the ODS conversion. The reaction time for ODS conversion is preferably 6 hours or more, particularly 12 hours or more. If the reaction time is too short, ODS groups cannot be sufficiently introduced to the surface of the porous glass particles. There is no particular limit to the upper limit of the reaction time, but since once the introduction of ODS groups has progressed to a certain extent, the ODS groups will not chemically bond to the surface of the porous glass particles even if the reaction is continued for a longer period, the reaction time is practically 48 hours or less.

[0057] After the reaction is completed, it is preferable to filter the porous glass particles from the reaction solution and wash the porous glass particles successively with toluene and methanol. By washing with toluene and methanol, reaction by-products such as pyridine hydrochloride and siloxane generated by the conversion of the porous glass particles to ODS can be removed.

[0058] It is preferable that the porous glass particles after ODS conversion are subjected to end-capping treatment (secondary silylation) to replace the remaining silanol groups with TMS groups. The end-capping treatment is preferably performed under toluene reflux using trimethylchlorosilane as a silane coupling agent and pyridine as a catalyst after thoroughly drying the ODS-converted porous glass particles at a temperature of 100°C or higher. The reaction time is preferably 6 hours or more, particularly 12 hours or more. If the reaction time is too short, the TMS groups cannot be sufficiently introduced onto the porous glass particle surface. There is no particular upper limit to the reaction time, but since once the introduction of the TMS groups has progressed to a certain extent, the TMS groups will not chemically bond to the porous glass particle surface even if the reaction is continued for any longer, the reaction time is practically 48 hours or less.

[0059] After the reaction is completed, it is preferable to filter the porous glass particles from the reaction solution and wash the porous glass particles with toluene and methanol in sequence. By washing with toluene and methanol, by-products such as pyridine hydrochloride and siloxane generated by the TMS conversion of the porous glass particles can be removed. In addition, from the viewpoint of reducing the remaining silanol groups on the inner pore surfaces of the porous glass particles, the above-mentioned end-capping treatment may be performed two or more times.

[0060] <Applications of solid phase extraction agents> The solid-phase extraction agent of the present invention is preferably used for residual pesticide analysis, and is particularly preferably used for the QuEChERS method and the STQ method.

[0061] The QuEChERS method consists of an extraction process, a salting-out process, a purification process, and an analysis and evaluation process for pesticides in food. In the extraction process, the food is crushed and homogenized, and then an organic solvent such as acetonitrile is added, and residual pesticides are extracted by shaking. In the salting-out process, salts such as magnesium sulfate (MgSO4), sodium chloride (NaCl), trisodium citrate, disodium citrate 1.5 hydrate, and sodium acetate (NaOAc) are added to the solution in which the organic solvent has been added and the pesticides have been extracted, and the solution is then shaken to separate the water and organic solvent. In this salting-out process, water-soluble impurities are removed by transferring to the aqueous phase, and the pesticides and other impurities contained in the food are transferred to the supernatant organic solvent phase. In the purification process, a portion of the supernatant liquid of the organic solvent phase separated in the salting-out process is collected, and a solid-phase extractant capable of adsorbing impurities is added to the solution, which is then shaken and centrifuged. In the final analysis and evaluation step, a portion of the supernatant of the solution obtained in the purification step is collected and analyzed using GC-MS / MS or LC-MS / MS to simultaneously analyze and evaluate the pesticides contained in the food. The solid-phase extraction agent of the present invention is preferably used in the purification step of the QuEChERS method. The solid-phase extraction agent of the present invention may also be used in combination with other solid-phase extraction agents such as PSA, ODS, GCB, and MgSO4.

[0062] The STQ method is a residual pesticide analysis method in which pesticides are extracted and salted out in the same manner as the QuEChERS method, then purified using a solid-phase extraction column, and simultaneously analyzed by GC-MS / MS or LC-MS / MS. The solid-phase extraction agent of the present invention is preferably used as a packing material for a solid-phase extraction column used in the purification step of the STQ method. The solid-phase extraction agent of the present invention may also be used in combination with a solid-phase extraction agent such as PSA, ODS, GCB, or MgSO4.

[0063] The residual pesticide analysis using the solid phase extraction agent of the present invention is preferably carried out for pesticides remaining in food. The food to be analyzed for residual pesticides is preferably fresh food or processed food, more specifically, fresh vegetables, fresh fruits, grains, beans, mushrooms, nuts, seeds, coffee beans, cocoa, tea, starch, vegetable processed products, fruit processed products, pickles, grain processed products, bean processed products, nut processed products, seed processed products, noodles, bread, chocolate, fruit drinks, coffee drinks, tea drinks, soy milk drinks, alcoholic beverages, edible oils and fats, etc. The pesticides to be analyzed for residual concentration in food are preferably insecticides, fungicides, insecticides and fungicides, herbicides, rodenticides, plant growth regulators, repellents, attractants, spreaders, medicines, quasi-drugs, etc. EXAMPLES

[0064] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples.

[0065] (Example 1: ODS-modified porous glass particles) <Glass base material preparation process> The solid-phase extraction agent consisting of porous glass particles was prepared by the following procedure. First, glass raw materials were placed in a platinum crucible so that the composition of the parent glass was, in mass%, SiO2 52.4%, Al2O3 2.6%, B2O3 17.5%, Na2O 5.2%, CaO 7.4%, ZrO2 11.0%, K2O 1.1%, PO 50.8%, and TiO2 2.0%, and melted at 1500°C for 3 hours. When melting the glass raw materials, they were stirred with a platinum rod and homogenized. Next, the molten glass was cast into a film by pouring it between a pair of cooling rollers.

[0066] <Precursor preparation process> The obtained film-like glass was pulverized in a ball mill and then classified with an air classifier to obtain precursor particles (glass particles) with an average particle size of 0.5 to 15 μm. The obtained precursor particles were fed into a furnace with a table feeder and heated with an air burner at 1000 to 3000 °C to soften and flow, thereby becoming approximately spherical.

[0067] <Porous process> 25 parts by mass of alumina fine particles (manufactured by Aerosil Co., Ltd.) with an average particle size of several tens of nm were added to 100 parts by mass of the roughly spherical precursor particles, and then heat-treated in an annealing furnace at 695°C for 10 hours to separate into two phases. In addition, the precursor particles after phase separation were immersed in 10% by mass hydrofluoric acid for 1 to 300 seconds to remove the altered layer (silica-rich phase) formed on the surface of the precursor particles.

[0068] Next, the precursor particles from which the altered layer had been removed were immersed in an acid solution to remove the boron oxide-rich phase. Specifically, the precursor particles were immersed in 1 mol / L nitric acid (95-99°C) for 0.5-5 hours, and then washed with ion-exchanged water. As an additional etching treatment, the precursor particles were immersed in 1.5 mol / L sulfuric acid (95-99°C) for 0.5-5 hours, and then washed with ion-exchanged water. The precursor particles were further immersed in a 0.5 mol / L aqueous sodium hydroxide solution (room temperature) for 0.5-5 hours, and then washed with ion-exchanged water.

[0069] When the obtained porous glass particles were observed with a FE-SEM (field emission scanning electron microscope, Hitachi SU-8220), the shape of the porous glass particles was found to be approximately spherical and the particles had a porous structure based on spinodal phase separation.

[0070] The composition of the obtained porous glass particles was analyzed by EDX (energy dispersive X-ray analyzer, EMAX Evolution EX-370 X-Max150, manufactured by Horiba, Ltd.) and the composition of the obtained porous glass particles was, in mass%, SiO2 79.5%, ZrO2 10.6%, Al2O3 2.9%, Na2O 1.2%, K2O 0.3%, CaO 2.8%, P2O5 0.9%, TiO2 1.8%, and B2O3+Na2O+K2O+CaO+P2O5+TiO2 7.0%.

[0071] Next, the pore size and specific surface area were measured using a pore size distribution analyzer (QUARASORB SI manufactured by Anton Paar). As a result, the pore size was 20.1 nm and the specific surface area was 144 m 2 / g.

[0072] <Surface modification process> Next, 1-10 g of porous glass particles dried at 150 ° C for 6 hours were dispersed in 20-200 mL of dry toluene, 0.5-7 g of dimethyloctadecylchlorosilane and 0.15-1.5 mL of pyridine were added, and the mixture was heated at toluene reflux temperature for 24 hours to prepare ODS-modified porous glass particles. The ODS-modified porous glass particles were filtered out from the reaction solution, washed with toluene and methanol in sequence, and dried at 120 ° C for 6 hours. Next, 1-10 g of ODS-modified porous glass particles were dispersed in 20-200 mL of dry toluene, 0.2-2 g of trimethylchlorosilane and 0.15-1.5 mL of pyridine were added, and the mixture was heated at toluene reflux temperature for 24 hours to perform end-capping of the ODS-modified porous glass particles. The porous glass particles were filtered out from the reaction solution, washed with toluene and methanol in sequence, and dried at 120 ° C for 6 hours. In this way, a solid-phase extraction agent consisting of ODS-modified porous glass particles was obtained.

[0073] (Example 2: SiO2-ZrO2-based porous glass plate for measuring solid acidity, Lewis acid point, and Bronsted acid point) <Evaluation of solid acidity of porous glass> A porous glass was prepared using a mother glass having the same composition as in the embodiment, and the solid acidity was evaluated. First, glass raw materials were placed in a platinum crucible so that the composition of the mother glass was, in mass%, SiO2 52.4%, Al2O3 2.6%, B2O3 17.5%, Na2O 5.2%, CaO 7.4%, ZrO2 11.0%, K2O 1.1%, P2O 50.8%, and TiO2 2.0%, and melted at 1500°C for 4 hours. When melting the glass raw materials, they were stirred using a platinum rod and homogenized. Next, the obtained molten glass was poured onto a metal plate and roll-formed into a plate shape, and then slowly cooled at 580°C to 540°C for 30 minutes to obtain a glass mother material.

[0074] The obtained glass base material was cut and polished to a size of 10 mm x 10 mm x 0.5 mm. Then, it was heat-treated in an electric furnace at 695 ° C for 12 hours to separate into two phases. The glass base material after phase separation was immersed in hydrofluoric acid for several seconds to several minutes to remove the heterogeneous layer on the surface. The glass base material after phase separation was immersed in 1 mol / L nitric acid (95 ° C) for 48 hours and then washed with ion-exchanged water. It was also immersed in 1.5 mol / L sulfuric acid (95 ° C) for 48 hours and then washed with ion-exchanged water. It was further immersed in 0.5 mol / L sodium hydroxide aqueous solution (room temperature) for 5 hours and then washed with ion-exchanged water.

[0075] When the obtained porous glasses were observed with a FE-SEM (field emission scanning electron microscope, Hitachi SU-8220), all the porous glasses were found to have a porous structure based on spinodal phase separation.

[0076] The composition of the obtained porous glass was analyzed by EDX (energy dispersive X-ray analyzer, EMAX Evolution EX-370 X-Max150 manufactured by Horiba, Ltd.). As a result, the composition of the obtained porous glass was, in mass%, SiO2 83.3%, ZrO2 10.6%, Al2O3 2.9%, Na2O 0.1%, K2O 0.1%, CaO 0.4%, PO51.6%, and TiO2 1.0%, and a SiO2-ZrO2-based porous glass plate containing the same amount of ZrO2 as in Example 1 was obtained.

[0077] Next, the solid acidity of the porous glass was evaluated by measuring the temperature-programmed desorption of ammonia (NH3). The porous glass was processed into pellets using a manual hydraulic pump (Riken Seiki Co., Ltd.) and a pellet molder (International Crystal Laboratories). The pellets were crushed in an agate mortar and classified into particle sizes ranging from 250 μm to 500 μm using a mesh sieve.

[0078] The classified sample was set in a catalyst / adsorbent evaluation device (BELCATII manufactured by Microtrack Bell Co., Ltd.) and pretreated by passing helium (He) at 500°C for 1 hour and 15 minutes. After cooling the sample to 100°C, 5% NH3 / He was passed through for 30 minutes. Next, He was passed through for 15 minutes, He containing water vapor was passed through for 30 minutes, and He was passed through again for 15 minutes. Finally, the sample was heated from 100°C to 500°C at 10°C / min while He was passing through, and the gas desorbed during the temperature rise was detected with a quadrupole mass spectrometer (BELMass manufactured by Microtrack Bell Co., Ltd.). The measurement conditions were a gas flow rate of 50sccm and a measurement mass number m / z=16. As a result of the temperature-programmed desorption measurement, the amount of NH3 desorbed per surface area was 0.745μmol / m 2 In addition, the peak of the NH3-TPD spectrum was observed at 230° C. Thus, the porous glass constituting the solid-phase extraction agent of the present invention is considered to have a strong solid acidity because it adsorbed a large amount of NH3.

[0079] In addition, the Lewis acid sites and Bronsted acid sites present on the surface of the porous glass plate were evaluated by pyridine adsorption FT-IR. First, the porous glass plate was pulverized into powder using a thoroughly washed agate mortar. Approximately 10 mg of the obtained porous glass powder was weighed and molded into a disk shape with a diameter of approximately 10 mm. After the disk-shaped sample was attached to the measurement device, it was heated to 500°C in a vacuum state, heated at 500°C for 1 hour, and then cooled to 150°C to measure the reference spectrum. Next, pyridine vapor was adsorbed on the sample at 150°C for 5 minutes, and then evacuated at 150°C for 60 minutes to remove excess pyridine. Then, the pyridine adsorption spectrum was measured using a Fourier transform infrared spectrophotometer Avatar360 (manufactured by Nicolet). The pyridine adsorption spectrum was measured under the following measurement conditions: a resolution of 4 cm -1 , 256 integrations, wavenumber range 4000-400cm -1 The temperature was 150°C. The spectrum was measured and found to be at 1576cm -1 The absorption peak of pyridine, which is thought to be adsorbed on the Lewis acid site, is 1545 cm -1 The absorption peak of pyridinium ions, which are thought to be generated by proton donation from Brønsted acid sites, was observed at the surface of the SiO2-ZrO2 porous glass. Therefore, it was confirmed that the SiO2-ZrO2 porous glass has Lewis acid sites and Brønsted acid sites on its surface.

[0080] (Comparative Example 1: Silica Gel) The solid acidity of silica gel was evaluated by measuring the temperature-programmed desorption of ammonia (NH3). Silica gel with SiO2 over 99% by mass was processed into pellets using a manual hydraulic pump (Riken Seiki Co., Ltd.) and a pellet molding machine (PIKE Technologies). The pellets were crushed in an agate mortar and classified using a sieve into particles with an average particle size ranging from 250 μm to 500 μm.

[0081] The classified sample was set in a catalyst / adsorbent evaluation device (BELCATII manufactured by Microtrack Bell Co., Ltd.) and pretreated by passing helium (He) at 500°C for 1 hour and 15 minutes. After cooling the sample to 100°C, 5% NH3 / He was passed through for 30 minutes. Next, He was passed through for 15 minutes, He containing water vapor was passed through for 30 minutes, and He was passed through again for 15 minutes. Finally, the sample was heated from 100°C to 500°C at 10°C / min while He was passing through, and the gas desorbed during the temperature rise was detected with a quadrupole mass spectrometer (BELMass manufactured by Microtrack Bell Co., Ltd.). The measurement conditions were a gas flow rate of 50sccm and a measurement mass number m / z = 16.

[0082] As a result of the temperature programmed desorption measurement, the detected value of the desorbed gas was below the quantifiable range of the calibration curve, so it was not possible to calculate the amount of desorbed gas from silica gel. Therefore, it is considered that the solid acidity of silica gel is weaker than that of porous glass. <Evaluation of pesticide adsorption properties> (Example 1-2: QuEChERS kit using ODS-modified porous glass particles) (Comparative Example 2: QuEChERS kit using PSA and ODS) The solid-phase extraction agent used in the QuEChERS method must be able to effectively adsorb impurity components, but it is also necessary that the adsorption capacity of the pesticide to be analyzed is small. Therefore, first, a QuEChERS kit using ODS-modified porous glass particles was prepared, and the pesticide adsorption characteristics were evaluated. Specifically, in Example 1-2, 50 mg of ODS-modified porous glass particles (Example 1) and 150 mg of MgSO4 (Cat. No. 137-12335, Wako Pure Chemical Industries) were weighed and added to a 2 mL centrifuge tube, and a QuEChERS kit using ODS-modified porous glass particles was prepared. In addition, in Comparative Example 2, the pesticide adsorption characteristics of a QuEChERS kit (Q-sep QuEChERS (dSEP for extract purification), Cat. No. 5065-40011, Restek) used in residual pesticide analysis was also evaluated, and it was confirmed whether ODS-modified porous glass particles can be used as a solid-phase extraction agent for the QuEChERS method. Comparative Example 2 is a QuEChERS kit in which three types of solid phase extraction agents, namely, 25 mg of ODS-modified silica gel (ODS), 25 mg of ethylenediamine-N-propylated silica gel (PSA), and 150 mg of MgSO4, are mixed in a 2 mL centrifuge tube.

[0083] To evaluate the pesticide adsorption characteristics, a pesticide mixed standard solution 63 (44 types of pesticides subject to the positive list system GC-MS) (34276-96, Kanto Chemical Co., Ltd.) was used as the pesticide mixed standard solution. The pesticides that can be evaluated using the pesticide mixed standard solution 63 are benzene hexachloride (δ-BHC), 4,4'-dichlorodiphenyldichloroethylene (4,4'-DDE), acetamiprid, isofenphos, isofenphos oxon, isoprocarb, ethiofencarb, ethoprophos, captafol, quinalphos, quinomethionate, chlorfenvinphos, diethofencarb, dichlorvos, cyhalothrin (λ), cypermethrin, dimethylvinphos, thenylchlor, and tetrachloroethane. Pesticide adsorption characteristics of fluthrin, deltamethrin, terbufos, triadimenol, tolclofos-methyl, paclobutrazol, bitertanol, pyridaben, pyrimidifen, pirimiphos-methyl, fenarimol, fensulfothion, butyrate, flucythrinate, flusilazole, flutolanil, fluvalinate, pretilachlor, propiconazole, bendiocarb, phosalone, malathion, methiocarb, metolachlor, mefenacet, and lenacil.

[0084] The pesticide mixed standard solution 63 was evaporated to dryness using an evaporator, and then redissolved in acetonitrile so that the pesticide concentration was 0.1 ppm. Next, 1 mL of the 0.1 ppm pesticide mixed solution was added to each of the QuEChERS kits of Example 1-2 and Comparative Example 2, shaken, and then centrifuged. The supernatant solution was then filtered, and the filtrate was analyzed three times by GC-MS / MS. In addition, the untreated 0.1 ppm pesticide mixed solution was also analyzed three times by GC-MS / MS.

[0085] The adsorption of pesticides to the solid-phase extraction agent was evaluated from the recovery rate of the pesticides. The recovery rate (%) was calculated using the peak area Se of each pesticide in the gas chromatograph of the solution obtained by adding 0.1 ppm pesticide mixture solution to the solid-phase extraction agent and shaking the solution, and the peak area Sr of each untreated pesticide, as the recovery rate (%) = 100·Se / Sr. The average value of the measurement results of three times was used for each pesticide peak area. In addition, according to the Ministry of Health, Labor and Welfare's "Guidelines for evaluating the validity of test methods for pesticides, etc., remaining in food" (Non-Patent Document 2), if the recovery rate of the pesticide is in the range of 70 to 120%, it can be analyzed without problems by GC-MS / MS, and the degree of adsorption of the pesticide was evaluated to be low.

[0086] The recovery rates of 44 types of pesticides are shown in Table 1. In Example 1-2, two types, isofenphos oxon and fensulfothion, and in Comparative Example 2, one type, quinomethionate, had recovery rates of less than 70%. It is considered highly likely that these components were adsorbed by the solid-phase extraction agent. On the other hand, the recovery rate of captafol exceeded 120% in both Example 1-2 and Comparative Example 2. This is thought to be due to the possibility that captafol was decomposed during treatment.

[0087] [Table 1]

[0088] Thus, the number of pesticides outside the range of recovery rates of 70 to 120% was three in Example 1-2 and two in Comparative Example 2, and the pesticide adsorption characteristics of Example 1-2 were at the same level as Comparative Example 2. Therefore, it is considered that the ODS-modified porous glass particles have a small pesticide adsorption capacity and meet the necessary conditions for a solid-phase extraction agent in the QuEChERS method.

[0089] <Analysis of pesticide residues in avocados and evaluation of pesticide recovery rate> Avocado contains a large amount of lipids, fatty acids, pigments, etc., so impurities have a large effect on the analysis, making it difficult to analyze residual pesticides. Currently, the impurities derived from avocado are often removed using PSA / ODS to purify residual pesticides. Therefore, the residual pesticide analysis in avocado was performed using the QuEChERS kits of Example 1-2 and Comparative Example 2, and the effect of differences in solid phase extraction agents on the measurement accuracy was evaluated by comparing the recovery rates of pesticides.

[0090] First, a matrix calibration curve was created to calculate the recovery rate. First, avocado (with the skin and the seed removed) was crushed and homogenized in a food processor, and extracted, salted out, and dehydrated using a QuEChERS extraction salt kit (Q-sep QuEChERS (extraction salt), Cat. No. 5065-40000, manufactured by Restek). The extraction, salting out, and dehydration of avocado were performed by adding 15 g of crushed and homogenized avocado and 15 mL of acetonitrile containing 1% acetic acid to a 50 mL centrifuge tube and shaking, and then adding an extraction salt mixture of 6 g of MgSO4 and 1.5 g of NaOAc (sodium acetate), shaking, and centrifuging. Next, 1 mL of the avocado extract (supernatant) that had been extracted, salted out, and dehydrated was added to each of the QuEChERS kits of Example 1-2 and Comparative Example 2, and shaking and centrifuging were performed. Then, 0.1 mL of the avocado solution purified using each of Example 1-2 and Comparative Example 2 was taken, and 0.025 mL of a pesticide mixed solution with different pesticide concentrations was added so that the pesticide concentrations were 0.01 ppm, 0.02 ppm, 0.04 ppm, 0.08 ppm, and 0.20 ppm, and these solutions were analyzed by GC-MS / MS. Here, the pesticide mixed solution added was prepared by evaporating the pesticide mixed standard solution 63 to dryness and redissolving it in acetonitrile containing 1% acetic acid. From the analysis results, when purification was performed using each of Example 1-2 and Comparative Example 2, a proportional relationship was confirmed between the pesticide concentration and the peak area, so a matrix calibration curve was created at five pesticide concentrations.

[0091] In preparing the matrix calibration curve, it was also confirmed that no pesticides were contained in the avocado solution after extraction and purification. Specifically, 0.025 mL of acetonitrile containing 1% acetic acid was added to 0.1 mL of the avocado solution that had been extracted, salted out, dehydrated, and purified in the same manner as above to match the calibration curve and matrix concentration, and the solution was analyzed using GC-MS / MS. As a result, no pesticides to be measured were detected in the avocado solution.

[0092] Next, the avocado solution to which the pesticides had been added was pretreated and analyzed, and the recovery rate of the pesticides was calculated using the matrix calibration curve. First, 15 g of crushed and homogenized avocado and 15 mL of a pesticide mixed solution, which was prepared by evaporating and drying the pesticide mixed standard solution 63 and redissolving it in acetonitrile containing 1% acetic acid, were added to a 50 mL centrifuge tube and shaken. The pesticide concentration was adjusted to 0.1 ppm. Then, an extraction salt containing 6 g of MgSO4 and 1.5 g of NaOAc (sodium acetate) was added, and the mixture was further shaken and centrifuged to extract, salt out, and dehydrate the avocado. Next, 1 mL of the avocado extract (supernatant) that had been extracted, salted out, and dehydrated was added to each of the QuEChERS kits of Example 1-2 and Comparative Example 2, and the mixture was shaken and centrifuged. In order to match the matrix concentration of the avocado solution used in the calibration curve, 0.025 mL of acetonitrile containing 1% acetic acid was added to 0.1 mL of the extracted and purified avocado solution, and the solution was analyzed once by GC-MS / MS, and the recovery rate (%) of each pesticide was calculated using the matrix calibration curve. The analysis of the pesticide recovery rate by the above procedure was performed three times for each of the cases using Example 1-2 and Comparative Example 2. The recovery rate (%) was calculated by averaging the results of the three times. The results are shown in Table 2. In Table 2, the number of pesticides with average recovery rates in the range of 70 to 120% was 27 types in Example 1-2 and 24 types in Comparative Example 2.

[0093] [Table 2]

[0094] Next, the absolute value |average recovery rate-100| was evaluated for the recovery rates of 43 types of pesticides, excluding Captafol, which is likely to have decomposed during pretreatment. The smaller this absolute value |average recovery rate-100| is, the closer the recovery rate is to 100%, meaning a better analysis result. The results are shown in Table 3. In Table 3, the number of pesticides where |average recovery rate-100| was Example 1-2<Comparative Example 2 was 29, Example 1-2=Comparative Example 2 was 1, and Example 1-2>Comparative Example 2 was 13, meaning that the pesticide recovery rate of Example 1-2 was better than that of Comparative Example 2.

[0095] [Table 3]

[0096] <Summary> From the above analysis results, in the residual pesticide analysis carried out on avocado, Example 1-2 had a better pesticide recovery rate for many pesticides than Comparative Example 2, and a highly accurate measurement result was obtained. On the other hand, Comparative Example 2 had a poorer pesticide recovery rate than Example 1-2 in the residual pesticide analysis carried out on avocado. Therefore, it is possible that the ODS-modified porous glass particles can adsorb impurities in avocado more effectively than PSA / ODS, improving the measurement accuracy of trace pesticide concentrations. This is thought to be due to the effective retention and adsorption effect of lipids, hydrophobic compounds, etc. by the ODS groups present on the surface of the porous glass particles, and the adsorption effect of impurities to the solid acid sites derived from ZrO2. Therefore, the ODS-modified porous glass particles can be suitably used as a purification adsorbent in the residual pesticide analysis of foods such as avocados that contain a large amount of lipids, fatty acids, pigments, etc. [Industrial Applicability]

[0097] The solid-phase extraction agent of the present invention is particularly suitable as an adsorbent for use in the purification process of residual pesticides in the QuEChERS method and the STQ method.

Claims

1. It is made of porous glass particles, and the glass composition is SiO 2 and ZrO 2 A solid phase extraction agent comprising:

2. The glass composition is, in mass%, SiO 2 70-95%, ZrO 2 More than 0 to 25%, Al 2 O 3 0-10%, B 2 O 3 +Na 2 O+K 2 O+CaO+P 2 O 5 + TiO 2 The solid-phase extraction agent according to claim 1, containing 0 to 15%.

3. The glass composition is, in mass%, SiO 2 70-90%, ZrO 2 10-25%, Al 2 O 3 0-10%, B 2 O 3 +Na 2 O+K 2 O+CaO+P 2 O 5 + TiO 2 The solid-phase extraction agent according to claim 2, containing 0 to 15%.

4. 3. The solid-phase extraction agent according to claim 1, wherein the particles have a substantially spherical shape.

5. Average particle diameter D 50 3. The solid-phase extraction agent according to claim 1, wherein the pore size is 0.1 to 300 μm and the pore size is 1 to 1000 nm.

6. Specific surface area is 10 to 800 m 2 The solid-phase extraction agent according to claim 1 or 2, wherein the CdSe is 0.01 to 0.15g.

7. 3. The solid-phase extraction agent according to claim 1, wherein the inner surface of the pores is provided with a hydrophobic functional group.

8. 8. The solid-phase extraction agent according to claim 7, wherein the hydrophobic functional group is an octadecylsilyl group and / or a trimethylsilyl group.

9. The solid-phase extraction agent according to claim 1 or 2, which is used for residual pesticide analysis.

10. The solid-phase extraction agent according to claim 9, wherein the pesticide residue analysis is performed by a QuEChERS method or an STQ method.

11. A method for producing the solid phase extraction agent according to claim 1 or 2, a base material preparation process for preparing a glass base material; A precursor preparation step of obtaining precursor particles by pulverizing the glass base material; a porosification step in which the precursor particles are heat-treated to separate them into two phases, and then one of the phases is removed with an acid solution to obtain porous glass particles; and A surface modification step using a silane coupling agent; A method for producing a solid phase extraction agent comprising the steps of: